Traversing philosophical boundaries - Hallman, Max O. (Wadsworth/Thomson, 2003)
TRAVERSING PHILOSOPHICAL BOUNDARIES is the most comprehensive multicultural text/reader for introductory philosophy. Addressing six primary philosophical concerns--the self, reality, epistemology, ethics, politics, and religion--this book contains not only many readings from the Western canon, but essential readings from many cultural perspectives not typically included in introductory philosophy classes as well. Asian, African, African-American, Latin American, and Feminist traditions are broadly represented and fully integrated into the exploration of these fundamental matters.